Tveganja za prekarnost pri študentskem delu - Franca, Valentina (Delavci in delodajalci, 2019)
The article focuses on legal analysis of student work with a special emphasis on determining elements of precarity. The findings indicate that in certain areas legal regulation provides appropriate legal protection of pupils and students against precarity, while in other areas they are more exposed to precarity. The question regarding the continuousness of work or concealed employment relationship therefore remains open.
Keywords: delovno razmerje; employment relationship; občasnost in začasnost dela; occasional and temporary work; precarity; prekarnost; social security; socialna varnost; student work; študentsko delo